DERIVATION OF POPULATION DISTRIBUTION BY COMBINING CENSUS AND LANDUSE DATA: AS AN INPUT FOR TSUNAMI RISK AND VULNERABILITY ASSESSMENT - M. Rokhis Khomarudin; Gunter Strunz; Joachim Post; Kai ZoBeder; Ralf Ludwing (BRIN, 2009)
Information on population distribution is crucial in distater risk management. Every disaster such as flood, drought, volcanic eruption, storm, earthquake and tsunamis implies theats to people with respect to loss of live, injury, and misery. Therefore, the information on detailed population distribution in the disaster or hazard zone is important in order to mitigate the impact of natural disasters. Moreover, accurate information on people exposure will help the goverment to improve the evacuation planning and to decrease the amount of people at risk. The available information on population distribution is mostly based on statistical data related to administrative boundaries, e.g. village, municipal, district, province, or national level. Within the border of adsministrative boundaries, the population is assumed to be distributed homogeneously within each unit area, even in the part of uninhabited areas e.g. lakes, forest, swamps, and areas with high slopes. Hence, this research focuses on the improvement of the available data on population distribution for the area along the west coast of Sumatera, south coast of Java and Bali. The results were used as an input for the tsunami risk assessment in the framework of the German-Indonesia Tsunami Early Warning System (GITEWS) project. Keyword: People distribution, spatial improvement, tsunami, remote sensing and GIS.